Service Quality Evaluation Under Bi-directional Perspective: An Initial Survey and Opportunities for Investigation - Agung Sutrisno; Ru (Jiun Shen) Lee Tzong (Jurnal Tekno Mesin, 2015)
Service quality is very important to improve competitive advantage of industrial organizations. This paper presents a summary on some research gaps within current service quality measurement models and explores the possibility to extend study on interactive service quality arena. The content of the paper is commenced by preliminary literature review to previous works related to service quality measurement models, interactive service quality, some observable gaps on interactive service quality measurement models. At conclusion, some directions for further studies are presented.